Utilization of Blood Products in Obstetric Patients at a Tertiary Care Hospital in Islamabad - Maqbool, Mishal; Khalid, Laila; Kausar, Zahra; Farooq, Naushin; Aslam, Sabeen; Zia, Zahida (Indus Journal of Bioscience Research, 2025)
The audit evaluated obstetric blood transfusion practices at a tertiary care hospital based in Islamabad regarding clinical appropriateness, safety, and efficiency related to the procedure. It involved 540 patients aged between 18 and 45 years with an even distribution in gravidity, parity, and antenatal booking status to demonstrate the findings’ generalizability. The many procedures included cesarean hysterectomies and emergency surgeries. There was a significant increase in pre- and post-transfusion hemoglobin levels, indicating positive and effective transfusion despite anemia and hemorrhage risk. Most transfusions were with red cell concentrates and fresh frozen plasma. Patterns indicate valid clinical need rather than wastage. A crossmatch-to-transfusion ratio (1.39) was achieved, indicating rational blood usage for transfusion. The average estimated blood loss of 846 mL justifies the frequency of blood transfusions, especially by intraoperative requirements (38.1%). Complications were found to be common postoperatively, constituting 49.3% of reactions from transfusion, and 48.9% required ICU admission. They stay complicated and lengthy because of this. Most often, surgical bleeding (27.2%) indicated a transfusion, followed by anemia (24.8%). Outcomes were evenly distributed over those parameters. Mortality, however, was high (26.5%). Age, blood group, and Rh factor did not significantly affect transfusions’ need for and outcome. Although normal data distributions do not exist, large samples make parametric analyses valid. Recommendations include infection control reinforcement, improved transfusion, and standard definition-based protocols for better maternal outcomes.